2008
DOI: 10.1007/s11265-008-0195-5
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Brain Deformation During Surgery Using Finite Element Method: Optimization and Comparison of Two Linear Models

Abstract: This paper addresses estimation of brain deformation during craniotomy using finite element modeling. Two mechanical models are optimized and compared for this purpose: linear solid-mechanic model and linear elastic model. Both models assume the realistic finite deformation of the brain after opening the skull. In this study, we use pre-operative and intra-operative magnetic resonance images (MRI) of five patients undergoing brain tumor surgery. Anatomical landmarks are identified by an expert radiologist on M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…It has been shown that such models provide numerical formulations that sufficiently describe brain tissue behaviour [3]. In addition, linear models are simpler to implement and run relatively fast.…”
Section: Linear Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that such models provide numerical formulations that sufficiently describe brain tissue behaviour [3]. In addition, linear models are simpler to implement and run relatively fast.…”
Section: Linear Modelmentioning
confidence: 99%
“…Some such models are linear and assume that the stress and strain relationship is linear, while others assume a non-linear relationship. Linear models assume that the brain's response to stress and strain is similar to that of elastic or solid materials [3]. A study by Hamidian et al proved that the solid mechanical model is more reliable than the elastic model.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional landmark-based methods usually detect relevant corresponding points or curves in two shapes, i.e., landmarking is essential in many shape registration and mapping applications [4], [5], [6], [7], [8], [9]. There are two drawbacks in this type of methods.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study [ 8 ], we used the finite element method to develop and compare two linear models: mechanical and elastic [ 9 - 12 ] for image-guided neurosurgery. We showed that accurate computation of brain deformation due to craniotomy can be achieved by defining a load through prescribed displacements of the corresponding points in the pre- and intra-operative images.…”
Section: Introductionmentioning
confidence: 99%